Susceptibility of fungi, mainly chocolate spot (Botrytis fabae sard.), to gamma irradiation in the faba bean crop (Vicia faba l.) - Aguilar-Luna, Jesús M. E.; López-López, Salvador; Loeza-Corte, Juan M. (Bioagro, 2020)
Fungi cause considerable losses in the faba bean crop in many regions of the world. The aim of the current research was to evaluate the susceptibility of faba bean to fungi, mainly chocolate spot, and its effect on yield, using seeds exposed to gamma irradiation. Faba bean seeds were cultivated in three regions: Hidalgo, Puebla and Tlaxcala, Mexico; the seeds were irradiated with a dose rate of 4.90 Gy·min-1 using a Gammacell 220 irradiator. The irradiation doses were 0, 20, 40, 60, 80, 160, 250 and 350 Gy of gamma rays with 60Co radioisotopes. The irradiated seeds showed acceptable germination (75.70 %) without visible damages, and survival was 53.62 % until 118 days after sowing. When unirradiated seed was used, the susceptibility of the crop could reach 60 % and the disease severity up to 34 %, with a disease progress rate of 0.006 units·day-1. The 40 Gy dose offered the best response to control the disease; up to 58.80 g of dry weight was obtained for every 100 seeds and a production of 4,442 kg·ha-1. In faba bean crop, up to 77 % of the variation in yield was due to severity of fungi, mainly the chocolate spot.